Novel spinel lithium ion battery positive electrode material and preparation method thereof
Through vanadium element modification and high-temperature solid phase synthesis method, the stability and energy density of the nickel-manganate lithium spinel positive electrode material are improved, the problems of manganese element dissolution and Jahn-Teller effect are solved, and high energy density and cyclic stability are achieved. Lithium-ion battery cathode material is suitable for power and consumer electronics applications.
Patent Information
- Application Number
- CN202411348731.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
Spinel type lithium nickel manganese oxide material has problems such as transition manganese dissolution, Jahn-Teller effect and electrolyte corrosion in lithium-ion battery applications, which limits its application as a mainstream positive electrode material.
High-energy density nickel-manganate lithium spinel positive electrode material modified with vanadium element can improve the stability and energy density of the material by adjusting the element ratio and high-temperature solid phase synthesis method, and reduce the proportion of manganese element to alleviate the disproportionation reaction and Jahn- Teller effect.
It effectively extends the cycle life of the material, improves the energy density and cycle stability, realizes the application of high-energy density lithium-ion battery positive electrode materials, and simplifies the preparation process, reduces costs, and is suitable for industrial production.
Smart Images

Figure CN119230814A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium electronic batteries, and in particular to a novel spinel lithium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] The existing novel spinel lithium-ion battery positive electrode materials and preparation methods still have the following disadvantages in actual use:
[0003] Lithium-ion batteries play an important role in power and energy storage due to their high power density, low self-discharge rate, and long cycle life. However, the capacity of lithium-ion batteries can no longer meet the development needs. An effective way to increase the energy density of batteries is to increase the working voltage and specific capacity of the positive electrode material (energy density = working voltage × specific capacity). Spinel lithium nickel manganese oxide (LiNi 0.5 Mn 1.504 , LNMO) has a high operating voltage (~4.7V vs.Li+ / Li) and a high discharge specific capacity (146.7mAh / g), an energy density of up to 650Wh / kg, and its low cost, high safety, and environmental friendliness make it one of the most promising positive electrode materials; however, spinel nickel manganese oxide materials also have shortcomings. In further applications, it has its own shortcomings such as transition metal manganese dissolution, Jahn-Teller effect, and corrosion of the electrolyte. This is the main reason why nickel manganese oxide cannot become the mainstream positive electrode material for lithium-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a novel spinel lithium ion battery positive electrode material and a preparation method thereof to solve the above-mentioned problems.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: a novel spinel lithium-ion battery positive electrode material and a preparation method, wherein the vanadium-modified high-energy-density lithium nickel manganese oxide spinel positive electrode material has the following chemical formula:
[0006] Li 1+2x Ni 0.5+x Mn 1.5-11x V 8x O4,0 <X<0.1363。
[0007] Furthermore, the high-valent elements are used to balance the electronegativity of the elements and improve the stability of the structure, thereby increasing the proportion of nickel to increase the discharge specific capacity.
[0008] Furthermore, the following steps are included:
[0009] (1) mixing a lithium source, a nickel source, a manganese source and a vanadium source by wet ball milling to obtain a mixed material precursor;
[0010] (2) heating the mixed precursor obtained in step (1) to 1000° C. at a heating rate of 1-10° C. / min for a first calcination for 24 hours, then cooling the temperature to room temperature at a cooling rate of 1-10° C. / min, and grinding the calcined product to obtain a novel spinel lithium ion positive electrode material having high energy density;
[0011] In step (1), the lithium source is lithium carbonate, lithium hydroxide or lithium oxide, the nickel source is nickelous oxide or nickel carbonate, the manganese source is manganese dioxide or manganese carbonate; and the vanadium source is vanadium pentoxide;
[0012] In step (1), the lithium source is lithium carbonate, the nickel source is nickelous oxide, and the manganese source is manganese dioxide;
[0013] In step (1), the molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is (1.22-1.23): 0.2: y: x, wherein 0 <x<0.5,y=1.5-11x;
[0014] The molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is 1.225:0.2:y:x, wherein 0 <x<0.5,y=1.5-11x;
[0015] The dispersion medium used in the wet ball milling mixing in step (1) is anhydrous ethanol;
[0016] The wet ball milling mixing in step (1) uses a ball-to-material weight ratio of 5:1-8:1, a ball milling speed of 300-600 rpm, and a ball milling time of 6-10 hours;
[0017] The application of new spinel lithium-ion battery materials with high energy density in power lithium batteries and lithium-ion batteries for consumer electronics.
[0018] Compared with the prior art, the novel spinel lithium-ion battery positive electrode material and preparation method provided by the present invention have the following beneficial effects:
[0019] The novel spinel lithium-ion battery positive electrode material and preparation method achieves a higher discharge specific capacity by extending the nickel (4.7V) platform;
[0020] The addition of appropriate pentavalent vanadium ions can effectively improve the stability of the material, extend the cycle life of the material, and improve its rate performance;
[0021] The proportion of manganese is reduced, and the disproportionation reaction and Jahn-Teller effect of manganese produced during the charge and discharge process are slowed down, thereby improving the energy density and cycle stability;
[0022] The spinel cathode material is a pure phase spinel structure, with high product purity, no impurity phase, and good product consistency;
[0023] The preparation method of spinel positive electrode material is a high-temperature solid-phase synthesis method. Compared with wet chemical synthesis methods such as co-precipitation, sol-gel method and hydrothermal method, the process is simple, easy to operate, low cost, and more conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0025] Figure 1 This is a scanning electron microscope image of the lithium nickel manganese oxide spinel positive electrode material obtained in Example 1 of the present invention;
[0026] Figure 2 This is a scanning electron microscope image of the lithium nickel manganese oxide spinel positive electrode material obtained in Example 2 of the present invention;
[0027] Figure 3 XRD diagram of the lithium nickel manganese oxide spinel positive electrode material obtained in Examples 1 and 2 of the present invention;
[0028] Figure 4 This is a cycle performance diagram of the lithium nickel manganese oxide spinel positive electrode material obtained in Examples 1 and 2 of the present invention at 1C (1C = 150 mAh / g);
[0029] Figure 5 The charge and discharge curves of the lithium nickel manganese oxide spinel positive electrode material obtained in Examples 1 and 2 of the present invention at 1C. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0031] See also Figure 1-5 A novel spinel lithium-ion battery positive electrode material and preparation method thereof, comprising a vanadium-modified high-energy-density lithium nickel manganese oxide spinel positive electrode material having the following general chemical formula:
[0032] Li 1+2x Ni 0.5+x Mn 1.5-11x V 8x O4,0 <X<0.1363。
[0033] By using high-price elements to balance the electronegativity of elements and improve the stability of the structure, the proportion of nickel is increased to increase the discharge capacity.
[0034] The steps include:
[0035] (1) mixing a lithium source, a nickel source, a manganese source and a vanadium source by wet ball milling to obtain a mixed material precursor;
[0036] (2) heating the mixed precursor obtained in step (1) to 1000° C. at a heating rate of 1-10° C. / min for a first calcination for 24 hours, then cooling the temperature to room temperature at a cooling rate of 1-10° C. / min, and grinding the calcined product to obtain a novel spinel lithium ion positive electrode material having high energy density;
[0037] In step (1), the lithium source is lithium carbonate, lithium hydroxide or lithium oxide, the nickel source is nickelous oxide or nickel carbonate, the manganese source is manganese dioxide or manganese carbonate; and the vanadium source is vanadium pentoxide;
[0038] In step (1), the lithium source is lithium carbonate, the nickel source is nickelous oxide, and the manganese source is manganese dioxide;
[0039] In step (1), the molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is (1.22-1.23): 0.2: y: x, wherein 0 <x<0.5,y=1.5-11x;
[0040] The molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is 1.225:0.2:y:x, wherein 0 <x<0.5,y=1.5-11x;
[0041] The dispersion medium used in the wet ball milling of the mixing material in step (1) is anhydrous ethanol;
[0042] In step (1), the ball-to-material weight ratio used in the wet ball milling is 5:1-8:1, the ball milling speed is 300-600 rpm, and the ball milling time is 6-10 hours;
[0043] Application of new spinel lithium-ion battery materials with high energy density in power lithium batteries and lithium-ion batteries for consumer electronics;
[0044] As mentioned above, the first aspect provides a vanadium-modified high energy density lithium nickel manganese oxide spinel positive electrode material with a general chemical formula of Li 1+2x Ni 0.5+x Mn 1.5-11x V 8x O4,0 <X<0.1363。
[0045] The second aspect provides a method for preparing the modified spinel lithium nickel manganese oxide of the first aspect, the method comprising the following steps:
[0046] (1) mixing a lithium source, a nickel source, a manganese source and a vanadium source by wet ball milling to obtain a mixed material precursor;
[0047] (2) heating the mixed precursor obtained in step (1) to 700-1000°C at a heating rate of 1-10°C / min for calcination for 18-24 hours, and then cooling to room temperature at a cooling rate of 1-10°C / min to obtain a vanadium-modified high-energy-density lithium nickel manganese oxide spinel positive electrode material having a general chemical formula of Li 1.05 Ni 0.525 V 0.2 Mn 1.225 O4.
[0048] In step (1), the lithium source may be lithium carbonate, lithium hydroxide, or lithium oxide; the nickel source may be nickelous oxide or nickel carbonate; and the manganese source may be manganese dioxide or manganese carbonate.
[0049] In step (1), the lithium source is lithium carbonate, the nickel source is nickelous oxide, the manganese source is manganese dioxide, and the vanadium source is vanadium pentoxide.
[0050] In step (1), the molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is (1.22-1.23):0.2:y:x, preferably 1.225:0.2:y:x, wherein 0 <x<0.5,y=1.5-11x。
[0051] In a preferred case, the amount of lithium source added is 1.03-1.08 times the target amount in terms of lithium element; it has been found that with the above amount added, the loss of lithium source volatilized during high-temperature calcination can be replenished, and appropriately increasing the lithium content can effectively improve the stability of the material and extend the cycle life of the material. Therefore, the amount added is generally controlled to be 1.03-1.08 times the target amount.
[0052] The amount of vanadium source used in the addition of vanadium element is controlled so that the obtained LiNi 0.5 Mn 1.5 O4-V x X<0.5; it has been found that if too little is added, the modification effect on lithium nickel manganese oxide is not obvious; if too much is added, although the stability will be improved, the capacity will be affected.
[0053] The conditions for wet ball milling mixing in step (1) at least meet the following requirements: the dispersion medium is anhydrous ethanol, and 30 ml of anhydrous ethanol is added.
[0054] There is no special requirement for the amount of dispersion medium added. For example, for a ball mill with a volume of 80 mL, the amount of dispersion medium added is 30-50 mL.
[0055] The conditions for wet ball milling mixing at least meet the following requirements: the ball-to-material weight ratio is 5:1-8:1, the ball-to-material weight ratio refers to the weight ratio of agate balls and raw materials, the ball milling speed is 400-600 rpm, and the ball milling time is 8-12 hours. It has been found that when the ball-to-material weight ratio is controlled at 5:1-8:1, the powder can be mixed and crushed more fully and the ineffective loss of energy can be avoided.
[0056] In step (2), the mixed precursor obtained in step (1) is heated to 1000°C at a heating rate of 1-10°C / min for the first calcination. The calcination time is 24 hours. The calcined product is ground to obtain a vanadium-modified high-energy-density lithium nickel manganese oxide spinel positive electrode material. It is found that under the above preferred conditions, the product structure can grow more fully, and oxygen deficiency in the product and the generation of impurity phases that affect the product uniformity and performance can be avoided.
[0057] The calcination operation is preferably carried out in a muffle furnace, and the specific heating process is: starting from room temperature, the temperature is uniformly increased at a heating rate, and maintained after reaching the calcination temperature;
[0058] The vanadium-modified high-energy-density lithium nickel manganese oxide spinel positive electrode material prepared by the above method has good cycle stability and rate performance, and the preparation method is simple in process, easy to operate, low in cost, and easy to industrialize.
[0059] Example 1
[0060] The pure phase high energy density lithium nickel manganese oxide spinel positive electrode material S1, denoted as LNMO, was prepared under laboratory conditions. The preparation method was as follows:
[0061] (1) 0.7837 g of lithium carbonate, 0.7469 g of nickel oxide, and 2.6345 g of manganese dioxide were added to a planetary ball mill, with anhydrous ethanol as the ball milling solvent, the added amount was 250 mL, and the ball-to-material weight ratio was 5:1, and the ball milling was performed at a speed of 400-600 rpm for 8 hours, and the mixture was fully mixed to obtain a mixed material precursor;
[0062] (2) The mixed precursor obtained in step (1) is placed in a muffle furnace. In an air atmosphere, the mixed precursor is heated to 1000°C at a heating rate of 5°C / min for the first calcination. The calcination time is 12 hours, and then the mixture is cooled to room temperature at a cooling rate of 1°C / min. The calcined product is ground to obtain a black high-energy-density lithium nickel manganese oxide spinel positive electrode material S1 without vanadium modification.
[0063] The battery assembly and test conditions are as follows:
[0064] (1) The high-energy-density lithium nickel manganese oxide spinel positive electrode material S1 obtained above without vanadium modification was uniformly mixed with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and then mixed and stirred in a degassing machine for 20 minutes to obtain a uniformly dispersed slurry. The obtained slurry was coated on a carbon-coated aluminum foil, and then vacuum-dried at 105°C for 12 hours and cut into circular electrode sheets with a diameter of 10 mm.
[0065] (2) Using 1 mol / L LiPF6 as the electrolyte, a polypropylene microporous membrane (Celgard2500) as the separator, and a metal lithium sheet as the negative electrode, the materials were made into a CR2032 button cell in a glove box filled with argon;
[0066] (3) At 25°C, constant current charge and discharge tests and rate tests were performed on button cells using the CT-4008Tn battery testing system from Shenzhen Xinwei Electronics Co., Ltd. The test voltage range was 3 V to 4.9 V.
[0067] Example 2
[0068] The vanadium-modified high energy density lithium nickel manganese oxide spinel positive electrode material S2, denoted as LNMO-V, is prepared according to the following steps:
[0069] (1) 0.7837 g of lithium carbonate, 0.7469 g of nickelous oxide, 2.5467 g of manganese dioxide, and 0.7945 g of vanadium pentoxide were added to a planetary ball mill, with anhydrous ethanol as the dispersion medium, the addition amount was 30 mL, the ball-to-material weight ratio was 5:1, and the ball milling was performed at a speed of 400-600 rpm for 8 hours, and the mixture was fully mixed to obtain a mixed material precursor;
[0070] (2) The mixed precursor obtained in step (1) is placed in a muffle furnace. In an air atmosphere, the mixed precursor is heated to 1000°C at a heating rate of 5°C / min for the first calcination. The calcination time is 24 hours, and then the mixture is cooled to room temperature at a cooling rate of 1°C / min. The calcined product is ground to obtain a black vanadium-modified high-energy-density lithium nickel manganese oxide spinel positive electrode material S2.
[0071] The assembly and testing conditions of the battery are the same as those in Example 1.
[0072] The present invention has carried out the following tests on embodiment 1,2:
[0073] like Figure 1 As shown, S1 obtained in Example 1 was subjected to scanning electron microscopy analysis, and it was found that the prepared spinel lithium nickel manganese oxide material was basically a typical octahedron, the particle size was basically within 4 μm, and the product had good consistency.
[0074] like Figure 2 As shown, S2 obtained in Example 2 was subjected to scanning electron microscopy analysis, and it was found that the prepared spinel lithium nickel manganese oxide material was basically a typical octahedron, the particles were larger than S1, the crystal surface was flat, and the product consistency was good.
[0075] like Figure 3 As shown, the lithium nickel manganese oxide spinel positive electrode materials obtained in Example 1 and Example 2 were subjected to XRD (X-ray diffraction) test; it was found that the XRD of Example 1 showed an obvious lithium nickel manganese oxide diffraction peak pattern, while in Example 2 it was found that the diffraction signal of lithium nickel manganese oxide was weakened at some peaks, and no other diffraction signals were observed on the XRD diagram except the diffraction peak of LNMO, indicating that V has basically entered the lattice of the LNMO material.
[0076] like Figure 4 As shown, the lithium nickel manganese oxide spinel positive electrode materials obtained in Examples 1-4 were subjected to a long cycle test at a 1C rate, and it was found that compared with Example 1, Example 2 showed better cycle stability, among which Example 2 had the best comprehensive electrochemical performance.
[0077] like Figure 5 As shown, the charge and discharge curves of the lithium nickel manganese oxide spinel positive electrode materials obtained in Example 1 and Example 2 were tested at a 1C rate, and it was found that after vanadium modification, the nickel element platform (4.7V) was effectively extended, and the discharge specific capacity was effectively improved.
[0078] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A novel spinel lithium-ion battery positive electrode material, characterized in that: The vanadium-modified high energy density lithium nickel manganese oxide spinel positive electrode material has the following general chemical formula: Li 1+2x Ni 0.5+x Mn 1.5-11x V 8x O4.0 <X<0.1363。 2. A novel spinel lithium-ion battery positive electrode material according to claim 1, characterized in that: The discharge specific capacity is increased by using high-valent elements to balance the electronegativity of the elements and improve the stability of the structure and increase the proportion of nickel.
3. The method for preparing a novel spinel lithium-ion battery positive electrode material according to claim 1, characterized in that: The steps include: (1) mixing a lithium source, a nickel source, a manganese source and a vanadium source by wet ball milling to obtain a mixed material precursor; (2) heating the mixed precursor obtained in step (1) to 1000° C. at a heating rate of 1-10° C. / min for a first calcination for 24 hours, then cooling the temperature to room temperature at a cooling rate of 1-10° C. / min, and grinding the calcined product to obtain a novel spinel lithium ion positive electrode material having high energy density; In step (1), the lithium source is lithium carbonate, lithium hydroxide or lithium oxide, the nickel source is nickelous oxide or nickel carbonate, the manganese source is manganese dioxide or manganese carbonate; and the vanadium source is vanadium pentoxide; In step (1), the lithium source is lithium carbonate, the nickel source is nickelous oxide, and the manganese source is manganese dioxide; In step (1), the molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is (1.22-1.23): 0.2: y: x, wherein 0 <x<0.5,y=1.5-11x; The molar ratio of the lithium source calculated as lithium element, the nickel source calculated as nickel element, the manganese source calculated as manganese element and the vanadium source calculated as vanadium element is 1.225:0.2:y:x, wherein 0 <x<0.5,y=1.5-11x; The dispersion medium used in the wet ball milling mixing in step (1) is anhydrous ethanol; The wet ball milling mixing in step (1) uses a ball-to-material weight ratio of 5:1-8:1, a ball milling speed of 300-600 rpm, and a ball milling time of 6-10 hours; The application of new spinel lithium-ion battery materials with high energy density in power lithium batteries and lithium-ion batteries for consumer electronics.
